Listening Comprehension and Listening Effort in the Primary School Classroom - Rudner, Mary; Lyberg-Åhlander, Viveka; Brännström, Jonas; Nirme, Jens; Pichora-Fuller, M. K.; Sahlén, Birgitta (Frontiers in Psychology, 2018)
In the primary school classroom, children are exposed to multiple factors that combine to create adverse conditions for listening to and understanding what the teacher is saying. Despite the ubiquity of these conditions, there is little knowledge concerning the way in which various factors combine to influence listening comprehension and the effortfulness of listening. The aim of the present study was to investigate the combined effects of background noise, voice quality, and visual cues on children’s listening comprehension and effort. To achieve this aim, we performed a set of four well-controlled, yet ecologically valid, experiments with 245 eight-year-old participants. Classroom listening conditions were simulated using a digitally animated talker with a dysphonic (hoarse) voice and background babble noise composed of several children talking. Results show that even low levels of babble noise interfere with listening comprehension, and there was some evidence that this effect was reduced by seeing the talker’s face. Dysphonia did not significantly reduce listening comprehension scores, but it was considered unpleasant and made listening seem difficult, probably by reducing motivation to listen. We found some evidence that listening comprehension performance under adverse conditions is positively associated with individual differences in executive function. Overall, these results suggest that multiple factors combine to influence listening comprehension and effort for child listeners in the primary school classroom. The constellation of these room, talker, modality, and listener factors should be taken into account in the planning and design of educational and learning activities.